1978
DOI: 10.1083/jcb.76.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Sites of lipoprotein particles in normal rat hepatocytes.

Abstract: Very low density lipoprotein (VLDL) particles are packaged by the Golgi apparatus into vacuoles which move to the plasma membrane and empty the particles into the space of Disse, via exocytosis. Traditionally, all lipoproteincontaining cisternae and vacuoles are thought to be parts of this pathway. Observations reported here demonstrate that there is a second population of lipoprotein-containing cisternae and vacuoles. This population is part of GERL, an organelle we consider to be a specialized hydrolase-rich… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
1

Year Published

1978
1978
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(34 citation statements)
references
References 33 publications
2
31
1
Order By: Relevance
“…The Golgi complex shown in the present study is different from those reported in other tissues which are relatively isolated structures from each other (2,14,16,(20)(21)(22)(23)(24) : in human and mouse cultured fibroblasts the stacks of the cisternal part of the Golgi complex are relatively isolated from each other, while the continuous network of the reticular part exists as if it combines the isolated cisternal parts, thus integrating the whole Golgi complex as a single elaborate network system. Although Novikoff et al (2 1) once suggested that the GERL is a continuous structure throughout the cytoplasm, they did not show any persuasive pictures .…”
Section: Monolayer Cell Ultracytochemistrycontrasting
confidence: 54%
See 2 more Smart Citations
“…The Golgi complex shown in the present study is different from those reported in other tissues which are relatively isolated structures from each other (2,14,16,(20)(21)(22)(23)(24) : in human and mouse cultured fibroblasts the stacks of the cisternal part of the Golgi complex are relatively isolated from each other, while the continuous network of the reticular part exists as if it combines the isolated cisternal parts, thus integrating the whole Golgi complex as a single elaborate network system. Although Novikoff et al (2 1) once suggested that the GERL is a continuous structure throughout the cytoplasm, they did not show any persuasive pictures .…”
Section: Monolayer Cell Ultracytochemistrycontrasting
confidence: 54%
“…They considered the GERL the site of the formation of lysosomes of various types (2,16,19) and also of secretory granules of various kinds (20,22,23). In the present study on cultured fibroblasts, it was also suggested that the reticular part of the Golgi complex (GERL) is the site of the formation of primary lysosomes of two types, the coated vesicle type and the regular dense body type.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Within the residual bodies, grains and other electron-opaque materials, presumably the result of intracellular digestion (9) The membrane of the lower AV2 appears compacted in areas and is therefore more electron-opaque. The possibility cannot be ruled out that the upper body labeled AV2 is a residual body derived from GERL, containing lipoprotein particles, in the manner described by Novikoff and Yam (10). The paired arrowheads indicate areas interpreted as glycogen's being internalized by microautophagy (9).…”
Section: Resultsmentioning
confidence: 99%
“…Kupffer cells contain high levels of lysosomal acid phosphatase, which is helpful for light and electron microscopy. 24 Cryoprotected frozen sections (10-20 m thick) were cut on a freezing microtome (Sartorious, Germany) and incubated at 37°C for 15 to 30 minutes in substrate mixture containing cytidine monophosphate (Sigma), acetate buffer, pH 5.0, and lead nitrate, as described previously. 24 After incubation, sections were rinsed in deionized water and incubated with ammonium sulfide.…”
Section: Methodsmentioning
confidence: 99%